The Comparative Effect of Imported (Biomin) and Local Iraqi Probiotic on Broiler Performance: Galib. A. AL-Kaissi , Rafid A. AL-Khalidi , S.A. Naji - AL-Kaissi, Galib A. (The Iraqi Journal of Veterinary Medicine, 2013)
Recent reports shown that the supplementation of the broiler ration with aprobiotic leads to an ideal microbial balance in the intestinal microflora of theirgastrointestinal tract. Such balance, however, would reflect on their health andperformance. The aim of the present study was to compare the effect of twoprobiotic products, Biomin and Iraqi probiotic, on the broiler performancecharacteristics. A total of 500 Lohman broiler chicks, one day old, wererandomly distributed into five dietary groups as follow:T1: chicks fed on diet with half dose of Biomin (1.5 Kg/ Ton diet).T2: chicks fed on diet with full dose of Biomin. (3 Kg/ Ton diet)T3: chicks fed on diet with half dose of Iraqi probiotic. (2.5 Kg/ Ton diet)T4: chicks fed on diet with full dose of Iraqi probiotic. (5 Kg/ Ton diet)T5: chicks fed slandered diet. (Control)Results obtained from the present study showed that the supplementation of thediets with probiotic, biomin or Iraqi probiotic, had significantly (ρ > 0.05)improved the final body weight, feed conversion and dressing percentage anddecreased mortality. However, Iraqi probiotic seemed to be more effective thanbiomin in most of these treats. Furthermore, the use of a half dose of Iraqiprobiotic (2.5 Kg / ton feed) seemed to be better than the full dose.